SOCIAL PREDICTORS OF DEPRESSIVE DISORDERS IN ADOLESCENTS (World Science, 2020)
The role of social-demographic and psychological factors in predicting of depressive disorder development in adolescents (infantilism, impaired cognitive social functioning, impaired family relations) is clarified. The role of psychotraumatic factors in the formation of depressive behavior disorder (violation of relations with peers and parents) is determined. The informative value of family environment, family adaptation indicators in the formation of depressive disorder in adolescents is determined.